INFLATION TARGETING REGIME IN MONETARY REFORMS - Yuldashev Farkhodbek Abdumutalibovich (European Science Publishing, 2025)
Many countries use the inflation targeting regime as an effective method of conducting monetary policy in the market economy. In accordance with the Decree of the President of the Republic of Uzbekistan “On improving monetary policy through a phased transition to an inflation targeting regime,” a number of measures were implemented. As a result, the achievements and shortcomings achieved, as well as some opinions and recommendations for their elimination, were presented.
Keywords: Inflation, inflation targeting, Republic of Uzbekistan, Central Bank, monetary policy, financial market, exchange rate, price.